Study the dimensions of leadership styles and personality characteristics and their relationship to the dimensions of Creative thinking for teachers of physical education in middle schools in Baghdad Governorate - Dawood Salman, Thaer (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to identify the dimensions of leadership patterns (initiation and interest in work, and caring about human relations), the dimensions of personality characteristics (control, responsibility, emotional and social balance), and the dimensions of innovative thinking (fluency, flexibility, and originality) among physical education teachers in middle schools in Baghdad Governorate. The study concluded that there is a great harmony and impact between the dimensions of leadership styles (initiation, interest in work, and care about human relations) with the dimensions of creative thinking (fluency, flexibility, and originality) among teachers of physical education in middle schools in Baghdad Governorate. The study recommended the need to pay attention to the final results that were reached by the middle school departments and in relation to the way they deal with physical education teachers. And to the necessity of conducting similar studies on physical education teachers in primary and middle schools in order to reach knowledge of the type of relationship between the dimensions of the three measures they have.